Donor/Recipient HLA Molecular Mismatch Scores Predict Primary Humoral and Cellular Alloimmunity in Kidney Transplantation - Meneghini, Maria; Crespo, Elena; Niemann, Matthias; Torija, Alba; Lloberas, Nuria; Pernin, Vincent; Fontova, Pere; Melilli, Edoardo; Favà, Alexandre; Montero, Nuria; Manonelles, Anna; Cruzado, Josep Maria; et al. (Frontiers in Immunology, 2021)
Donor/recipient molecular HLA mismatch predicts primary B-cell alloimmune activation, yet the impact on de novo donor-specific T-cell alloimmunity (dnDST) remains undetermined. The hypothesis of our study is that donor/recipient HLA mismatches assessed at the molecular level may also influence a higher susceptibility to the development of posttransplant primary T-cell alloimmunity. In this prospective observational study, 169 consecutive kidney transplant recipients without preformed donor-specific antibodies (DSA) and with high resolution donor/recipient HLA typing were evaluated for HLA molecular mismatch scores using different informatic algorithms (amino acid mismatch, Eplet MM and Predicted Indirectly Recognizable HLA Epitopes [PIRCHE-II]). Primary donor-specific alloimmune activation over the first 2 years posttransplantation was assessed by means of both dnDSA and dnDST using single antigen bead (SAB) and IFN- ELISPOT assays, respectively. Also, the predominant alloantigen presenting pathway priming DST alloimmunity and the contribution of main alloreactive T-cell subsets further characterized in vitro. Pretransplantation, 78/169 (46%) were DST+ whereas 91/169 (54%) DST-. At 2-years, 54/169 (32%) patients showed detectable DST responses: 23/54 (42%) dnDST and 31/54 (57%) persistently positive (persistDST+). 24/169 (14%) patients developed dnDSA. A strong correlation was observed between the three distinct molecular mismatch scores and they all accurately predicted dnDSA formation, in particular at the DQ locus. Likewise, HLA molecular incompatibility predicted the advent of dnDST, especially when assessed by PIRCHE-II score (OR 1.014 95%CI 1.001-1.03, p=0.04). While pretransplant DST predicted the development of posttransplant BPAR (OR 5.18, 95%CI=1.64-16.34, p=0.005) and particularly T cell mediated rejection (OR 5.33, 95%CI=1.45-19.66, p=0.012), patients developing dnDST were at significantly higher risk of subsequent dnDSA formation (HR 2.64, 95%CI=1.08-6.45, p=0.03). In vitro experiments showed that unlike preformed DST that is predominantly primed by CD8+ direct pathway T cells, posttransplant DST may also be activated by the indirect pathway of alloantigen presentation, and predominantly driven by CD4+ alloreactive T cells in an important proportion of patients. De novo donor-specific cellular alloreactivity seems to precede subsequent humoral alloimmune activation and is influenced by a poor donor/recipient HLA molecular matching.